Letter to the editor - Cortical spreading depression - San Juan Orta, Daniel; Jaramillo-Gonzalez, Andres; Díaz-Peregrino, Roberto; Olivares-Rivera, Arturo; Santos, Edgar (Journal of neurosurgery, 2017)
"Letter to the Editor: Cortical spreading depression" published on Jan 2017 by American Association of Neurological Surgeons.